The African factory worker. A sample study of the life and labour of the urban African worker. By the Department of Economics, University of Natal. [With a pref. by H.R. Burrows and G.C. Scully] (Oxford University Press, 1950)
Report no. 2 of the Durban Economic Research Committee.